Phenotypic spectrum of BLM‐ and RMI1‐related Bloom syndrome. Issue 5 (11th March 2022) - Gönenc, Ipek Ilgin; Elcioglu, Nursel H.; Martinez Grijalva, Carolina; Aras, Seda; Großmann, Nadine; Praulich, Inka; Altmüller, Janine; Kaulfuß, Silke; Li, Yun; Nürnberg, Peter; Burfeind, Peter; Yigit, Gökhan; et al.
Abstract: Bloom syndrome (BS) is an autosomal recessive disorder with characteristic clinical features of primary microcephaly, growth deficiency, cancer predisposition, and immunodeficiency. Here, we report the clinical and molecular findings of eight patients from six families diagnosed with BS. We identified causative pathogenic variants in all families including three different variants in BLM and one variant in RMI1 . The homozygous c.581_582delTT;p.Phe194* and c.3164G>C;p.Cys1055Ser variants in BLM have already been reported in BS patients, while the c.572_573delGA;p.Arg191Lysfs*4 variant is novel. Additionally, we present the detailed clinical characteristics of two cases with BS in which we previously identified the biallelic loss‐of‐function variant c.1255_1259delAAGAA;p.Lys419Leufs*5 in RMI1 . All BS patients had primary microcephaly, intrauterine growth delay, and short stature, presenting the phenotypic hallmarks of BS. However, skin lesions and upper airway infections were observed only in some of the patients. Overall, patients with pathogenic BLM variants had a more severe BS phenotype compared to patients carrying the pathogenic variants in RMI1, especially in terms of immunodeficiency, which should be considered as one of the most important phenotypic characteristics of BS. Abstract : Phenotypic features of Bloom syndrome differ in severity between patients carrying pathogenic variants in BLM and RMI1 .